(untitled) (Journal of the College of Basic Education, 2022)
In this work the new operations matrix was derived for Multi Discrete Laguerre Wavelets Transform (MDLWT) with the dimension and this matrix was derived by the integrals of the functions that obtained from the mother function or the mother wave. This matrix is the coefficients matrix of the developed multi wavelet and this wavelet was applied in image processing using the Matlab program, where a new program was built that applies to many of the images and examples the proposed wave efficiency. In addition, MSE and PSNR were calculated and good results were compared to the previous methods.